WAYS AND MEANS OF ENRICHMENT OF VOCABULARY IN LEARNING VOCABULARY OF STUDENTS OF THE RUSSIAN LANGUAGE - M. F. Davletmukhametova (Journal Park Publishing, 2022)
This article discusses the role of expanding the active vocabulary of younger students in the lessons of the Russian language, the impact of its formation on the development of primary school students, as well as the role of a primary school teacher in the formation of students' vocabulary. The results of an express study of the level of enrichment of the vocabulary of younger schoolchildren are described in detail. The purpose of this express study is to determine the level of active vocabulary of younger students. The study was conducted at the bases of SGOSH No. 18 in the Tashkent region. The period of this study is four academic weeks (February - March 2021 - 2022 academic year). The results of diagnostics of the initial level of enrichment of the vocabulary and the intermediate result are given, subsequent results will be revealed at the end of the study. The article also describes in detail the methods aimed at identifying the level of vocabulary of younger students, provides types of exercises aimed at this problem, and also provides examples of exercises used in the work on enriching vocabulary within the framework of the school educational program. Several ways of selecting words in order to create a lexical minimum and their features are also given.
Keywords: junior schoolchild; vocabulary; lexical exercises